Microbial lipid accumulation through bioremediation of palm oil mill effluent using a yeast-bacteria co-culture - Karim, Ahasanul; M., Amirul Islam; Zaied, Khalid; Yousuf, Abu; Khan, Md. Maksudur Rahman; Che Ku Mohammad Faizal, Che Ku Yahya (Elsevier, 2021)
Co-cultures of different microorganisms are considered promising inocula for treating palm oil mill effluents (POME) and producing value-added bio-products (e.g., biofuels and fatty acid-derived materials). However, the efficiency of yeast-bacteria co-culture for microbial lipid production through bioremediation of wastewater remains a bottleneck. In this study, the performance of a co-culture for lipid accumulation through POME bioremediation was investigated using a yeast (Lipomyces starkeyi) and a bacterium (Bacillus cereus). A maximum biomass of 8.89 ± 0.33 g/L and lipid production of 2.27 ± 0.10 g/L were achieved by the co-culture inoculum, which were substantially higher than those of the monocultures. Besides, the co-culture inoculum attained a maximum chemical oxygen demand (COD) removal of 83.66 ± 1.9%, while the individual cultures of B. cereus and L. starkeyi obtained 74.35 ± 1.7% and 69.01 ± 2.3%, respectively. The bioremediation efficiency was confirmed by the seed germination index (GI) of Vigna radiata (Mung bean). It was observed that the co-culture inoculum had a higher GI compared to the untreated POME and even the monoculture-treated POME. We argue that the symbiotic association of a yeast-bacteria co-culture in POME could be an attractive approach for achieving maximum biomass as well as lipid production and simultaneous bioremediation of POME